2014
DOI: 10.1159/000355349
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Contribute to Age-Associated Changes in Peripheral T-Cell Homeostasis Acting in a Thymus-Independent Way

Abstract: Objective: Considering a causal role of androgens in thymic involution, age-related remodeling of peripheral T-cell compartments in the absence of testicular hormones was evaluated. Methods: Rats were orchidectomized (ORX) at the age of 1 month, and T-peripheral blood lymphocytes (PBLs) and splenocytes from young (75-day-old) and aged (24-month-old) rats were examined for differentiation/activation and immunoregulatory marker expression. Results: In ORX rats, following the initial rise, the counts of CD4+ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 106 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…1). Additionally, we found that gonadectomy-induced thymic rejuvenation is associated with a substantial rise in the frequency of CD25+FoxP3+ cells among CD4+CD8single positive thymocytes in rats [150,151]. On the other hand, we have recently revealed that the frequency of CD25+FoxP3+ cells among CD8+CD4-single positive thymocytes increases with aging in male and female rats, so it is comparable between old female and male rats [53,120].…”
Section: Aging Influences the Generation Of Tregs In Thymusmentioning
confidence: 70%
“…1). Additionally, we found that gonadectomy-induced thymic rejuvenation is associated with a substantial rise in the frequency of CD25+FoxP3+ cells among CD4+CD8single positive thymocytes in rats [150,151]. On the other hand, we have recently revealed that the frequency of CD25+FoxP3+ cells among CD8+CD4-single positive thymocytes increases with aging in male and female rats, so it is comparable between old female and male rats [53,120].…”
Section: Aging Influences the Generation Of Tregs In Thymusmentioning
confidence: 70%
“…Castration of post-pubertal male mice showcases an increase in T cell levels in secondary lymphoid tissues and enhanced T cell proliferation (Ref. 80 ). Bongen et al .…”
Section: Immune Characteristics In Sexual Maturity: Mature and Differ...mentioning
confidence: 99%
“…This dysfunction is associated with down-regulation of surface expression of CD247, the TCR ζ chain, which could be followed by flow cytometry (68). Another candidate should be CD4+CD25+ T regulatory (Treg) cells, whose functions and fitness are critical to maintain immunologic balance, including inflammation (92), as accumulating evidence suggests that their frequencies are increased in the elderly and experimental animals, and shown to play a crucial role in aging and age-related diseases (93)(94)(95)(96)(97)(98). Therefore, the analysis of their frequency and functional properties could provide sensitive biomarkers of inflammatory status during aging.…”
Section: Biomarkers For Low-grade Chronic Inflammationmentioning
confidence: 99%